O ọfò de exu e os caminhos de ogun: o samba que vem de lá de são mateus pede passagem - Carmo, Fabiana Marques do (2023)
The allure of wordsintroduces us back to the magic of Samba, guiding us along its stronghold’s pathwys. São Mateus’s Samba, which has produced numerous contributions to Brazilian Popular Music (MPB), from the 90's to the present day, fosters an ongoing dialogue between the new generation and the local Samba griots. The Afro-Brazilian culture’s triad, consisting of religiosity, dances and musicality/Samba, plays a significant role in the country's cultural, social, and historical development. Despite the often overlooked and diminished contributions of the Afro and Indigenous ethnic groups to the Brazilian socio-historical and cultural context, due to colonialism and racial stereotypes, their presence is increasingly vibrant and palpable with each manifestation, exhibiting unmistakable characteristics. Decolonial studies caution against power dynamics that foster universalisms based on a false understanding of a homogenized reality, which for a long time denied global cultural diversities, leading to epistemicides that disadvantage peoples who have suffered from European colonization. n. In light of the geopolitics of the knowledge of marginalized groups, the current scientific work “The ọfò of Exú and the paths of Ogum: the Samba that comes from t São Mateus asks for passage”, aims to study the stronghold of São Mateus's Samba and understand the socio-spatial and cultural constructs led by social actors. This is done from the perspective survival as a form of resistance, initiated in social struggles to ensure the right to life, employing 'Samba wheels' as a tool for political awareness to foster the socio-cultural and territorial transformation of the São Mateus district. Methodologically, the study adopts the framework of ethnography, enablingus to fulfill the specific objectives of sharing the memories of São Mateus's social actors who have helped establish this territoryas one of Brazil's largest Samba strongholds.